Reinventing Konsep Hifdzi al-Bi’ah pada Maqashid as-Shari’ah dalam Green Financing - Parmujianto, Parmujianto (Al Yasini : Jurnal Keislaman, Sosial, hukum dan Pendidikan, 2024)
This study aims to develop the concept of hifdzi bi'ah in maqasid as-shari'ah and analyze its implications on green financing policies. This study uses the literature study method and document analysis to examine the concept of hifdzi al-bi'ah and its relevance to green financing. The results of the study show that the concept of hifdzi al-bi'ah can be an ethical and moral foundation in the development of sustainable and environmentally friendly green financing policies. This study also found that the implementation of the concept of hifdzi al-bi'ah in green financing can increase awareness and concern for the environment and reduce the negative impact of economic activities on the environment. This study recommends that the concept of hifdzi al-bi'ah can be integrated into green financing policies in sustainable economic development.